Methodological Contribution to Effectivity Studies of Training Programs in Community Mental Health Promotion - Ittzés, András; Csáky-Pallavicini, Roger; Tomcsányi, Teodóra (European Journal of Mental Health, 2007)
Our paper is a survey of the methodology of two effectivity studies of postgraduate training in community mental health promotion in Hungary. The aims of our study of the Helping Relationship Course were multifaceted: we intended to measure how much the student internalised a philosophy of non-directive counselling, the recognition of the client’s non-verbalised emotions and the possibilities of application of the helping relationship promoting community mental health, as well as the skills of reflecting on group behaviour. This was realised by means of a written case study. In the Appendix of our paper we also bring the evaluation questionnaire. In the Activity Supervising Course, the various helping activities and their representatives are introduced. Within the frame of the effectivity study we followed the impact of these presentations on representatives of other professions. Teachers and pastors were in the focus of the study: essays written on provocative questions concerning these two professional groups were content analysed, comparing the answers of different student cohorts (freshmen and graduates). In the case of both studies we briefly demonstrate the content and the form of the course discussed. This is followed by showing the specific aims and methods of the study in more detail, including the methods of collecting material and analysing data.